Enhancing Public Health Messaging: Discrete-Choice Experiment Evidence on the Design of HIV Testing Messages in China. (July 2019) - Durvasula, Maya; Pan, Stephen W.; Ong, Jason J.; Tang, Weiming; Cao, Bolin; Liu, Chuncheng; Terris-Prestholt, Fern; Tucker, Joseph D.
Introduction . While a growing literature documents the effectiveness of public health messaging on social media, our understanding of the factors that encourage individuals to engage with and share messages is limited. In the context of human immunodeficiency virus (HIV) among men who have sex with men (MSM) in China, rising incidence and low testing rates despite decades of interventions suggest the need for effective, targeted messaging to reach underserved populations. Social media platforms and sex-seeking apps present a promising avenue, as web-based strategies can take advantage of existing trust within dense social networks.Methods . We conducted an online discrete-choice experiment in January 2017 with MSM from across China. Participants were presented with 6 choice tasks, each composed of 2 messages about HIV testing, and were asked in which scenario they were more likely to share the content. Participants were given information about the source of the HIV testing message, the social media sharing platform, and the recipients with whom they would share the message. They were given the option of sharing 1 message or neither. Multinomial and mixed logit models were used to model preferences within 4 subgroups.Results . In total, 885 MSM joined the survey, completing 4387 choice tasks. The most important attribute for 3 of the 4 subgroups was social media sharing platform. Men were more willing to share messages on sex-seeking mobile applications and less willing to share materials on generic (non-MSM) social media platforms. We found that men with more active online presences were less willing to share HIV testing messages on generic social media platforms.Conclusions . Our findings suggest that sex-seeking platforms represent a targeted, efficient method of actively engaging MSM in public health interventions.